"Des responses et rencontres": Frank Speech and Self- Knowledge in Guillaume Bouchet's Serées - O'Sullivan, Luke (Renaissance and reformation, 2020)
Guillaume Bouchet's Serées (1584, 1597, 1598) constitute an exercise in commonplacing framed as a collection of tales told around a Poitevin dining table. They engage in a form of quasi-philosophical thinking staged by and for an urban merchant community, the social world in which Bouchet operated. The second book opens with a discussion of frank speech. Writing amid civil war, Bouchet takes up this "chatouilleux" subject by turning to Plutarch, the classical authority on parrhesia (truth-telling). Recycling Plutarch, though, Bouchet does not ask how or when to speak frankly but instead examines responses to "franchise" both in the tales and from the storytellers themselves. Around Bouchet's table, talk of frank speech leads to awkward silences and conversation grinding to a halt. This serée illuminates a context for parrhesia distinct from the familiar arena of nobles counselling autocrats or performing "liberté." Here, philosophical self-knowledge slips uncomfortably into a feeling of social selfconsciousness, revealing a distinct conception of the ethics and epistemologies surrounding frankness. (English)